A New approach to coordinated urgan area development - JICA.; JPBD. (1995.)
Shows the different stages of land readjustment project in Malaysia.
AV production by Digi Art Production
Keywords: Urbanization -- Malaysia; Sustainable development -- Malaysia; Land use, Urban -- Malaysia